miR-1247-3p regulation of CCND1 affects chemoresistance in colorectal cancer. - Dequan Wang; Jielian Wang; Fei Yao; Zhufu Xie; Jianze Wu; Huiguang Chen; Qingming Wu (PLoS ONE)
The effectiveness of chemotherapy involving 5-fluorouracil and cisplatin (DDP) for the treatment of colorectal cancer (CRC) is often limited due to the emergence of drug resistance. An increasing body of research highlights the crucial role of abnormally expressed microRNAs (miR/miRNAs) in fostering drug resistance in various types of cancer. The present study was the first to explore the potential roles and mechanisms of the small non-coding RNA miR-1247-3p in CRC, particularly its association with DDP resistance in CRC. The findings of the current study revealed a significant decrease in miR-1247-3p expression in CRC cells, especially those resistant to drugs. By contrast, there was a marked increase in the expression of cyclin D1 (CCND1), a known target gene of miR-1247-3p that is negatively regulated by this miRNA. By modulating CCND1, miR-1247-3p can effectively reduce drug resistance and promote apoptosis in CRC cells, suggesting that miR-1247-3p could potentially reduce chemotherapy resistance by targeting CCND1. These results highlight the pivotal role of miR-1247-3p in reducing chemotherapy resistance through the inhibition of CCND1, providing insight into a promising therapeutic strategy for overcoming CRC resistance.